Hubungan antara harga diri dengan perilaku Pada penderita tuberculosis (tb) paru - Yuliana. S - -; Fathra Annis Nauli; Riri - Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
Pulmonary tuberculosis patient had a problem of self-esteem and their behavior. This research aims to examine the relationship between self-esteem and patient’s behavior against pulmonary tuberculosis problems at Arifin Achmad Hospital Pekanbaru. In this study, researcher uses description correlation method with cross sectional approach. The total number of respondent was 30 choosen by purposive sampling technique. The instrument was questionnaire that has been tested for validity and reliability. The data were analyzed by univariate and bivariate analysis. The results showed a significant relationship between self-esteem and patient’s behavior with pulmonary tuberculosis problems at Arifin Achmad Hospital Pekanbaru(p value 0,001). Based on the result, it is recommended to provide psychosocial nursing care on self-esteem and health education on hygienic behavior to decrease the incidence infection of pulmonary tuberculosis. Keywords: behavior, patients with pulmonary tuberculosis, self-esteem.